Dietary protein requirement in common snook (Centropomus undecimalis ) juveniles reared in marine and brackish water - Concha-Frías, Bartolo; Alvarez González, Carlos Alfonso; Gaxiola, Gabriela; Chiappa, Xavier; Sánchez-Zamora, Adolfo; Martínez-García, Rafael; Camarillo-Coop, Susana; Peña, Emyr; Jiménez-Martínez, Luis Daniel; De la Cruz-Alvarado, Fanny Janet (Ecosistemas y Recursos Agropecuarios, 2018)
A total of 300 Centropomus undecimalis juveniles, with an average initial weight of 3.16 0.28 g and average total length of 7.17 0.22 cm, were reared for eight weeks using a recirculating system to determine the dietary protein requirement for their growth and survival. The eect of ve experimental diets containing 40, 45, 50, 55 and 60% total protein content and two salinities (brackish water, BW at 5 UPS and marine water, MW at 36 UPS) were assessed. Fish were fed ve times per day at 2.5% of total biomass. All treatments were performed in triplicate,recording the individual weight and total length every 15 d, while weight gain and daily growth rate were recorded at the end of the experiment. Mean weight increased proportionally as protein content increased, with the greatest growth occurring with a 60% protein diet for sh reared in brackish water, and 55% for sh in marine water. We consider that the protein requirement in C. undecimalisjuveniles is high; in addition, it differs depending on the salinity,